Monitoring Resistance of Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) to Insecticides by Using Encapsulated Artificial Diet Bioassay - Cristiane Maria Tibola; Leandro Silva; Fernanda Sgubin; Celso Omoto (Insects, 2021)
The novel ingestion bioassay method was developed for detecting and monitoring resistance of Euschistus heros by encapsulating an artificial liquid diet using Parafilm®. This methodology was compared with the tarsal contact (vial test) and topical application methods for thiamethoxam, imidacloprid, and lambda-cyhalothrin. The best bioassay method for the neonicotinoid insecticides thiamethoxam and imidacloprid was ingestion. For pyrethroid insecticide lambda-cyhalothrin, the best result was obtained by topical application. Using the best bioassay method for each insecticide, the susceptibility to these insecticides was monitored in 30 populations of E. heros collected from soybean crops in Brazil from 2018 to 2020. High variations in susceptibility to thiamethoxam (resistance ratios, 1.6–22 times), imidacloprid (resistance ratios, 1.6–22 times), and lambda-cyhalothrin (resistance ratios, 5–40 times) were detected among the evaluated E. heros populations. In order to monitor the susceptibility of E. heros to insecticides, diagnostic concentrations were defined based on the LC99 of the susceptible reference population: 5.65 µL of a.i./mL for thiamethoxam, 12.45 µL of a.i./mL for imidacloprid, and 0.20 µg of a.i./insect for lambda-cyhalothrin. Subsequently, we select an E. heros strain resistant to neonicotinoid insecticides and another to lambda-cyhalothrin. The resistance ratios obtained after seven selection cycles were 66, 41 and 44 times for thiamethoxam, imidacloprid and lambda-cyhalothrin, respectively.